Tinjauan Normatif Terhadap Perlindungan Saksi Dan Korban Dalam Kasus Lingkungan Studi Kasus Pembunuhan Salim Kancil Di Lumajang - Mohamad Ilham Romadlon (Journal of Contemporary Law Studies, 2026)
This study aims to examine the legal framework governing witness and victim protection in Indonesia and to analyze state accountability for the failure to provide protection in the Salim Kancil case in Lumajang. The study employs normative legal research using statutory and conceptual approaches. Legal materials consist of primary, secondary, and tertiary sources collected through literature review and analyzed qualitatively. The findings demonstrate that witness and victim protection in Indonesia has been normatively regulated through Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 on Witness and Victim Protection. The law places the state and the Witness and Victim Protection Agency (LPSK) as central actors responsible for ensuring legal security, protection, and fulfillment of victims’ rights. Nevertheless, the murder of Salim Kancil reflects weaknesses in the implementation of protection mechanisms, particularly in environmental crime cases involving economic and political interests. The failure to provide adequate protection indicates state negligence and generates constitutional, administrative, civil, and ethical responsibility for law enforcement institutions. This study concludes that strengthening institutional coordination, preventive protection mechanisms, and state accountability is essential to ensure effective witness and victim protection within the criminal justice system.